KOMUNIKASI ANTARAGAMA MASYARAKAT PERUMAHAN DALAM PELESTARIAN LINGKUNGAN HIDUP - Amrullah Ali Moebin (LP2M IAIN Tulungagung, 2022)
This study aims to determine the practice of interfaith communication in residential communities in making efforts to preserve the environment. The research uses an ethnographic approach and is located in two cities, namely Tuban and Tulungagung Regencies. Researchers stayed for five years, starting in 2017-2021. Three years in Tuban, two years in Tulungagung. The results of this study indicate that not all housing communities are individualistic, but some are collectivist. Their interfaith communication patterns are mutually tolerant of each other. To protect the environment, they jointly make a schedule for cleaning the environment and managing waste.